The notion of place, place meaning and identity in urban regeneration - Ujang, Norsidah; Zakariya, Khalilah (Elsevier, 2015)
Urban regeneration within traditional settings has transformed places and constructed meanings embedded in the existing social and cultural settings. Thus, the social and emotional meanings, attached to or evoked by the elements of the urban environment were at least as important, often more so than the structural and the physical aspects of people imagery. This paper reviews the definitions and concept of place in establishing a conceptual framework for urban regeneration in light of the sense of place and environmental psychology (place attachment) principles. The reviews highlight the importance of place-based approach and principles in the era of urban regeneration and its implication on the continuity of place meaning and identity in the Asian context. This paper advocates the importance of the psychological dimension of place in regenerating urban setting for psychological well-being of the inhabitants.